The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/5732046
|View full text |Cite
|
Sign up to set email alerts
|

Global Occupational Exposure to Blood and Body Fluids among Healthcare Workers: Systematic Review and Meta-Analysis

Abstract: Background. Occupational exposure to blood and body fluids has become a serious public health problem for healthcare workers and is a major risk for the transmission of various infections such as human immune-deficiency virus, hepatitis B virus, and hepatitis C virus. This systematic review and meta-analysis aims to determine the career time and previous one-year global pooled prevalence of occupational exposure to blood and body fluids among healthcare workers. Methods. For the review, the articles published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 45 publications
0
17
0
2
Order By: Relevance
“…Although strict adoption of universal precautions has decreased high-risk exposure to HIV in the last two decades, the prevalence may be much higher than expected due to possible underreporting [ 40 , 41 ]. Two systematic reviews [ 42 , 43 ] reported a high worldwide prevalence of needlestick injuries. Exposure to blood or body fluids in the healthcare setting were 56.2% and 56.6% during career time and 32.4% and 39% in the previous year, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although strict adoption of universal precautions has decreased high-risk exposure to HIV in the last two decades, the prevalence may be much higher than expected due to possible underreporting [ 40 , 41 ]. Two systematic reviews [ 42 , 43 ] reported a high worldwide prevalence of needlestick injuries. Exposure to blood or body fluids in the healthcare setting were 56.2% and 56.6% during career time and 32.4% and 39% in the previous year, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The actual sample size for the study was determined using a single population proportion formula { n = [(zα/2) 2 p(1−p)]/d 2 }, n = sample size, z α/2 = 95% confidence level, P = the proportion of HIV-positive HCWs among post exposure to BBFs in the previous study (48.2%), 19 d = margin of error (0.05). By considering 10% of non-response rate, the final sample size of the study was 422.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the highest patient flow, nurses are overloaded, so they are at the highest risk of such exposure at emergency department. 2 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations